Pemasangan Lampu Penerangan Jalan Dan Running Text Pada Gapura Perumahan Landungsari Indah Kabupaten Malang - Mochammad Mieftah; Dhimas Dhesah Kharisma; Rahman Azis Prasojo; Epiwardi Epiwardi; Anang Dasa Novfowan (Jurnal Pengabdian kepada Masyarakat, 2022)
The installation of lighting and running text in the housing gate is expected to provide lighting around the gate so that it is clearly seen if there are vehicles passing by. In addition, with the upgrade of the information board using an electronic board (running text) it becomes very clear and beautiful both in the morning and at night.